The Distribution of Power in The Recruitment of Prospective Head Area by PDI-P in The Election Year 2015 Jember - Amwaritama, Mimin (Government Studies of Muhammadiyah Malang University/AIPPTM, 2018)
The distribution of power is still a debate in the party's internal politics, especially in terms of recruitment of candidates for regional elections head. Yet the existence of a clear policy related settings portion of authority between the Centre Party and the party in an area is often the cause of difference of interests and the decision appeared, particularly the matter of flying a candidate head of the region. The implication is unavoidable political dynamics. This paper seeks to analyse thoroughly about the distribution of power in the political candidate recruitment head area in PDI-P Jember. The focus of the writing refers to the moment of the Election Year 2015 Jember. Analysis of peeled through the perspective of the theory of political recruitment and distribution of power. The results of the analysis gave an explanation that is not yet a clear subject control distribution of power in the sphere of internal party candidacy candidate in terms of the head area. This implies the existence of the political dynamics of differences at each level of the process candidacy. When the populist nature of the power distribution then the process candidacy running electorate with a more democratic, more inclusive, as well as the representation of social groups can be more assured. Meanwhile, when the distribution of power are elitist by rising degree of exclusivity of candidacy political interests, opportunities to appear much larger due to the interaction between the candidates with the electorate became more and more intensive